School Work

8 pages
780 views

Fundamentals of Logic Design 7th Edition Roth Solutions Manual

of 8
All materials on our website are shared by users. If you have any questions about copyright issues, please report us to resolve them. We are always happy to assist you.
Share
Description
Fundamentals of Logic Design 7th Edition Roth Solutions Manual Download at:https://goo.gl/ZfGdGQ fundamentals of logic design 7th edition solutions pdf fundamentals of logic design 7th edition answer key fundamentals of logic design solutions manual pdf roth fundamentals of logic design 7th fundamentals of logic design 6th edition solutions manual pdf roth fundamentals of logic design 7th solutions pdf fundamentals of logic design 7th edition solutions manual pdf roth fundamentals of logic design 7th solutions manual pdf
Transcript
    Fundamentals of Logic Design 7th Edition Roth SOLUTIONS MANUAL Full download at: http://testbanklive.com/download/fundamentals-of-logic-design-7th-edition-roth-solutions-manual/  Unit 2 Problem Solutions   2.1   See FLD p. 731 for solution.   2.2 (a) In both cases, if X = 0, the transmission is 0, and if  X = 1, the transmission is 1.  2.2 (b) In both cases, if X = 0, the transmission is YZ, and if X = 1, the transmission is 1.    X X  X X     X    2.3      X Y     Answer is in FLD p. 731   Y Z Y Z    2.4 (a)   2.5 (a)   2.6 (a)    F = [(  A· 1) + (  A· 1)] + E + BCD = A + E + BCD  (  A + B ) ( C + B ) (  D' + B ) (  ACD' + E  )  = (  AC + B ) (  D' + B ) (  ACD' + E  ) By Dist. Law  = (  ACD' + B ) (  ACD' + E  ) By Dist. Law  = ACD' + BE By Dist. Law   AB + C'D' = (  AB + C'  ) (  AB + D'  )  = (  A + C'  ) (  B + C'  ) (  A + D'  ) (  B + D'  )  2.4 (b)   2.5 (b)   2.6 (b)   Y = (  AB' + (  AB + B ))  B + A = (  AB' + B )  B + A   = (  A + B )  B + A = AB + B + A = A + B  (  A' + B + C'  ) (  A' + C' + D ) (  B' + D'  )  = (  A' + C' + BD ) (  B' + D'  ) {By Distributive Law with  X = A' + C'  }  = A'B' + B'C' + B'BD + A'D' + C'D' + BDD'    = A'B' + A'D' + C'B' + C'D'    WX + WY'X + ZYX = X  ( W + WY' + ZY  )  = X  ( W + ZY  ) {By Absorption}  = X  ( W +Z  ) ( W + Y  ) 2.6 (c)   2.6 (e)   2.7 (a)    A'BC + EF + DEF' = A'BC + E  (  F +DF'  )  = A'BC + E  (  F +D ) = (  A'BC + E  ) (  A'BC + F + D )  = (  A' + E  ) (  B + E  ) ( C + E  ) (  A' + F + D ) (  B + F + D ) ( C + F + D )   ACD' + C'D' + A'C = D' (  AC + C'  ) + A'C    = D' (  A + C'  ) + A'C By Elimination Theorem  = (  D' + A'C  ) (  A + C' + A'C  )  = (  D' + A'  ) (  D' + C  ) (  A + C' + A'  ) By Distributive Law and Elimination Theorem  = (  A' + D'  ) ( C + D'  ) (  A + B + C + D ) (  A + B + C + E  ) (  A + B + C + F  )  = A + B + C + DEF   Apply second Distributive Law twice   D   2.6 (d)   2.6 (f)   2.7 (b)    XYZ + W'Z + XQ'Z = Z  (  XY + W' + XQ'  )  = Z  [ W' + X  ( Y + Q'  )]  = Z  ( W' + X  ) ( W' + Y + Q'  ) By Distributive Law   A + BC + DE    = (  A + BC + D )(  A + BC + E  )  = (  A + B + D )(  A + C + D )(  A + B + E  )(  A + C + E  )  WXYZ + VXYZ + UXYZ = XYZ ( W + V + U  ) By first Distributive Law  U   E V     F  A B W Y    C  Z  2.8 (a)   2.8 (c)   2.9 (a)  [(  AB ) ' + C'D ] ' =  AB ( C'D ) ' = AB ( C + D'  )  = ABC + ABD'   ((  A + B'  ) C  ) ' (  A + B ) ( C + A ) '       = (  A'B + C'  ) (  A +  B ) C'A' = (  A'B + C'  )  A'BC'    = A'BC'     F = [(  A + B ) ' + (  A + (  A +  B ) '  ) '  ] (  A + (  A + B ) '  ) '    = (  A + (  A +  B ) '  ) '   By Elimination Theorem with   X= (  A+ (  A+B ) '  ) ' = A'  (  A + B ) = A'B   2.8 (b)   2.9 (b)  [  A + B ( C' +  D )] ' =  A'  (  B ( C' +  D )) '    =  A'  (  B' + ( C' +  D ) '  ) =  A'  (  B' + CD'  )  =  A'B' +  A'CD'   G = {[(R + S + T)' PT(R + S)']' T}'  =  (  R + S  + T  ) '   P T  (  R + S  ) '  + T '    = T' + (  R'S 'T'  )  P  (  R'S'  ) T = T' + PR'S'T'T = T'     2.10 (a)  X Y     X    2.10 (b)  X    Y X Y    2.10 (c)   2.10 (e)    X Y'     X     X ' Y     X X     X     Z Y  Z     X    Y'    2.10 (d)  A   C     A  B    A   C '    B    B   2.10 (f)  X  X X    Y Z Y Z Y  2.11 (a)   2.11 (c)   2.11 (e)  (  A' + B' + C  )(  A' + B' + C  ) ' = 0 By Complementarity Law   AB + ( C' + D )(  AB ) ' = AB + C' + D  By Elimination Theorem [  AB' + ( C + D ) ' +E'F  ]( C + D ) =  AB'  ( C + D ) + E'F  ( C + D ) Distributive Law  2.11 (b)   2.11 (d)   2.11 (f)    AB ( C' + D ) + B ( C' + D ) = B ( C' + D ) By Absorption (  A'BF + CD'  )(  A'BF + CEG ) = A'BF + CD'EG  By Distributive Law   A'  (  B + C  )(  D'E + F  ) ' + (  D'E + F  )  = A'  (  B + C  ) + D'E + F By Elimination 2.12 (a)   2.12 (c)   2.12 (e)   2.13 (a)   2.13 (c)   2.14 (a)   2.15 (a)   2.16 (a)   2.17 (a)   2.17 (c)  (  X + Y'Z  ) + (  X + Y'Z  ) ' = 1 By Complementarity Law ( V'W + UX  ) ' ( UX + Y + Z + V'W  ) = ( V'W + UX  ) '   ( Y + Z  ) By Elimination Theorem ( W' + X  )( Y + Z'  ) + ( W' + X  ) '  ( Y + Z'  )  = ( Y + Z'  ) By Uniting Theorem   F  1 = A'A + B + (  B + B ) = 0 + B + B = B    F  3 = [(  AB + C  ) 'D ][(  AB + C  ) + D ]  = (  AB + C  ) 'D (  AB + C  ) + (  AB + C  ) ' D   = (  AB + C  ) ' D By Absorption   ACF  (  B + E + D )   f ' = {[  A + (  BCD ) '  ][(  AD ) ' + B ( C' + A )]} '    = [  A + (  BCD ) '  ] ' + [(  AD ) ' + B ( C' + A )] '    = A'  (  BCD ) '' + (  AD ) ''  [  B ( C' + A )] '    = A'BCD + AD [  B' + ( C' + A ) '  ]  = A'BCD + AD [  B' + C''A'  ]  = A'BCD + AD [  B' + CA'  ]   f D = [  A + (  BCD ) '  ][(  AD ) ' + B ( C' + A )]  D   = [  A (  B + C + D ) '  ] + [(  A + D ) '  (  B + C'A )]   f = [(  A' + B ) C  ] + [  A (  B + C'  )]  = A'C + B'C + AB + AC'    = A'C + B'C + AB + AC' + BC    = A'C + C + AB + AC' = C + AB + A = C + A    f = (  A' + B' + A )(  A + C  )(  A' + B' + C' + B ) (  B + C + C'  ) = (  A + C  )  2.12 (b)   2.12 (d)   2.12 (f)   2.13 (b)   2.13 (d)   2.14 (b)   2.15(b)   2.16 (b)   2.17 (b)   2.18 (a)  [ W + X'  ( Y +Z  )][ W' + X' ( Y + Z  )] = X'  ( Y + Z  ) By Uniting Theorem ( UV' + W'X  )( UV' + W'X + Y'Z  ) = UV' + W'X   By Absorption Theorem ( V' + U + W  )[( W + X  ) + Y + UZ'  ] + [( W + X  ) + UZ' + Y  ] = ( W + X  ) + UZ' + Y By Absorption   F  2 = A'A' + AB' = A' + AB' = A' + B'     Z = [(  A + B ) C  ] ' + (  A + B ) CD = [(  A + B ) C  ] ' + D  By Elimination with  X = [(  A + B ) C  ] '    = A'B' + C' + D' W + Y + Z + VUX     f ' = [  AB'C + (  A' + B + D )(  ABD' + B'  )] '    = (  AB'C  ) '  [(  A' + B + D )(  ABD' + B'  ] '    = (  A' + B'' + C'  )[(  A' + B + D ) ' + (  ABD'  ) 'B''  ]  = (  A' + B + C'  )[  A''B'D' + (  A' + B' + D''  )  B ]  = (  A' + B + C'  )[  AB'D' + (  A' + B' + D )  B ]   f D = [  AB'C + (  A' + B + D )(  ABD' + B'  )] D  = (  A + B' + C  )[  A'BD + (  A + B + D' )  B'  )   f = A'C + B'C + AB + AC' = A + C    product term, sum-of-products, product-of-sums)    = D (  A' + B' + AC' )( C + AC' ) 0 0 0 0 0 0  = D (  A' + B' + C' )( C + A ) 0 0 1 1 1 x  0 1 0 1 0 1   D  B'   1 0 0 0 0 0  C'   1 1 0 0 0 0  1 1 1 1 1 x  2.18 (b)   2.18 (d)  sum-of-products sum term, sum-of-products, product-of-sums  2.18 (c)   2.18 (e)  none apply  product-of-sums  2.19 W     Z +   +    X Y     Z    W     X Y +   2.20 (a)   2.20 (b)   F     F = D [(  A' + B' ) C + AC' ]   F = D [(  A' + B' ) C + AC' ]  = A' CD + B' CD +AC' D    A ' C D  B ' C D    A C' D   2.20 (c)    F = D [(  A' + B' ) C + AC' ]  2.21  A B C H F G    A'    2.22 (a)   2.22 (b)   2.22 (c)   2.23 (a)    A'B' + A'CD + A'DE'    = A'  (  B' + CD + DE'  )  = A'  [  B' + D ( C + E'  )]  = A'  (  B' + D )(  B' + C + E'  )   H'I' + JK    = (  H'I' + J  )(  H'I' + K  )  = (  H' + J  )(  I' + J  )(  H' + K  )(  I' + K  )   A'BC + AB'C + CD'    = C  (  A'B + AB' + D'  )  = C  [(  A + B )(  A' + B'  ) + D'  ]  = C  (  A + B + D'  )(  A' + B' + D'  )  W + U'YV = ( W + U'  )( W + Y  )( W + V  )  2.22 (d)   2.22 (e)   2.22 (f)   2.23 (b)    A'B' + ( CD' + E  ) = A'B' + ( C + E  )(  D' + E  )  = (  A'B' + C + E  )(  A'B' + D' + E  )  = (  A' + C + E  )(  B' + C + E  ) (  A' + D' + E  )(  B' + D' + E  )   A'B'C + B'CD' + EF' = A'B'C + B'CD' + EF'    = B'C (  A' + D'  ) + EF'    = (  B'C + EF'  )(  A' + D' + EF'  )  = (  B' + E  )(  B' + F'  )( C + E  )( C + F' ) (  A' + D' + E  )(  A' + D' + F'  )  WX'Y + W'X' + W'Y' = X'  ( WY + W'  ) + W'Y'    = X'  ( W' + Y  ) + W'Y'    = (  X' + W'  )(  X' + Y'  )( W' + Y + W'  )( W' + Y + Y'  )  = (  X' + W'  )(  X' + Y'  )( W' + Y  )  TW + UY' + V    = ( T+U+Z  )( T+Y'+V  )( W+U+V  )( W+Y'+V  )   2.23 (c)    A'B'C + B'CD' + B'E' = B'  (  A'C + CD' + E'  )  = B'  [  E' + C  (  A' + D'  )]  = B'  (  E' + C  )(  E' + A' + D'  )  2.23 (d)    ABC + ADE' + ABF' = A (  BC + DE' + BF'  )  = A [  DE' + B ( C + F'  )]  = A (  DE' + B )(  DE' + C + F'  )  = A (  B + D )(  B + E'  )( C + F' + D )( C + F' + E'  )
We Need Your Support
Thank you for visiting our website and your interest in our free products and services. We are nonprofit website to share and download documents. To the running of this website, we need your help to support us.

Thanks to everyone for your continued support.

No, Thanks
SAVE OUR EARTH

We need your sign to support Project to invent "SMART AND CONTROLLABLE REFLECTIVE BALLOONS" to cover the Sun and Save Our Earth.

More details...

Sign Now!

We are very appreciated for your Prompt Action!

x